Fine Mapping of a Novel Major Quantitative Trait Locus, qPAA7, That Controls Panicle Apical Abortion in Rice - Wang, Xiaolei; Li, Lingfeng; Sun, Xiaotang; Xu, Jie; Ouyang, Linjuan; Bian, Jianmin; Chen, Xiaorong; Li, Weixing; Peng, Xiaosong; Hu, Lifang; Cai, Yicong; Zhou, Dahu; et al. (Frontiers in Plant Science, 2021)
Panicle apical abortion (PAA) phenomenon often occurs in rice production and severely restricts increases in rice yield, but little is known about the genetic basis of PAA. In this study, we identified PAA quantitative trait loci (QTL) in three environments by using a set of chromosome segment substitution lines (CSSL) constructed from a cross between indica Changhui121 as the recurrent parent and japonica Koshihikari as the donor parent. The results identified a total of 10 QTLs on chromosomes 1, 3, 4, 5, 7, 9 and 11. Among these QTLs, qPAA3, qPAA4.1 and qPAA7 were identified in all three environments, and these QTLs account for 4.26%, 6.85% and 26.96% of the phenotypic variation, respectively. The results showed that qPAA7 is a major effector locus. Therefore, we selected a serious PAA strain CSSL176, which harbours the qPAA7 allele, to construct an F2 population with Changhui 121, and verify the genetic stability of qPAA7. Next, qPAA7 was finally finely mapped to the 73.8 kb interval of chromosome 7 by analyzing the phenotype and genotype of F2 and F3. According to the annotation results, qRT-PCR data analysis and comparison of the genome sequences of CH121, Koshihikari and CSSL176, found that LOC_Os07g41220 and LOC_Os07g41280 are most likely target genes of the qPAA7. The results of this study lay a foundation for cloning and regulatory mechanisms of PAA.